Distribution and accumulation of zinc and nitrogen in wheat grain pearling fractions in response to foliar zinc and soil nitrogen applications - Pan-pan ZHANG; Yu-lu CHEN; Chen-yang WANG; Geng MA; Jun-jie LÜ; Jing-bao LIU; Tian-cai GUO (Journal of Integrative Agriculture)
Increasing zinc (Zn) concentration in wheat grain is important to minimize human dietary Zn deficiency. This study aimed to investigate the effect of foliar Zn and soil nitrogen (N) applications on the accumulation and distribution of N and Zn in grain pearling fractions, N remobilization, and the relationships between nutrient concentration in the vegetative tissues and grain or its fractions in two cropping years in the North China Plain. The results showed a progressive decrease in N and Zn concentrations from the outer to the inner parts of grain, with most of the accumulation in the core endosperm. Foliar Zn application significantly increased N concentration in the pericarp, and soil N application increased N concentration in each grain fraction. Both treatments significantly increased core endosperm Zn concentration. Foliar Zn had no effect on grain N and Zn distribution. Soil N application made N concentrated in the aleurone, promoted Zn translocation to the core endosperm and also increased N remobilization and its efficiency from the shoot to the grain, but no improved contribution to grain was found. N concentration in grain and its fractions were positively correlated with N in vegetative organs at anthesis and maturity, while positive correlations were obtained between N concentration in the pericarp and progressive central area of the endosperm and Zn concentration in the core endosperm. Thus, foliar Zn and soil N applications effectively increased yield and N and Zn concentrations in the wheat grain, particularly in the endosperm, and could be promising strategies to address Zn deficiency.